(untitled) (Journal of Rangpur Medical College, 2024)
Symbol is a conventional sign in writing or printing, represents something else that is invisible. When one examines the trademarks of numerous medical organizations, will discover the photographs of single or double snakes spherical rods are used interchangeably. Between the two most popular medical symbols either single or double snake, it is interesting to know that one is being the classical and true sign of medicine while the other one’s association is rather doubtful. The origins and creation of those symbols in medical sciences are pretty different, and as a consequence it’s important to take a look at the ancient occasions that connected them with the medical profession. J Rang Med Col. September 2024; Vol. 9, No. 2: 89-93